Asuhan Keperawatan Pada Ny.Y Dengan Post Sectio Caesarea Indikasi Disproporsi Kepala Panggul Di Bangsal Bougenvile RS T IV Slamet Riyadi Surakarta - Puji Astuti, Dewi; , Winarsih Nur Ambarwati, S.Kep, Ns, ETN, M.Kep (2015)
NURSING CARE OF Mrs.Y WITH POST SECTIO CAESAREA INDICATION CEPHALOPELVIK DISPROPORTION AT SHED BOUGENFIL RS T IV SLAMET RIYADI SURAKARTA (Dewi Puji Astuti, 2015, 65 pages) ABSTRACT Background: Sectio Caesarea is common problem in hospital with one of cause is Cephalopelvik Disproporttion, namely relative imbalance between the size of the baby and the size the pelvis. Aim of Research: To study about nursing care on client with post sectio caesarea indication cephalopelvik disproportion including assesment, intervention, implementation, and evaluation. Result: After implementation of nursing care for 3x24 hours, it was found that the pain level decreased from 5 to 2, there are no signs of infection, ASI has not been met to the fullest. Conculsion: In the implementations of nursing care required collaboration between client, family, and other medical personnel, so nursing care that patients receive the maximum. Key Word: Sectio Caesarea, Cephalopelvik Disproportion, pain, risk of infection, ineffectiveness breast feeders.